Engaging 'hard to reach' groups in health promotion: the views of older people and professionals from a qualitative study in England - Ann E. M. Liljas; Kate Walters; Ana Jovicic; Steve Iliffe; Jill Manthorpe; Claire Goodman; Kalpa Kharicha (BMC, 2019)
Abstract Background Older people living in deprived areas, from black and minority ethnic groups (BME) or aged over 85 years (oldest old) are recognised as 'hard to reach'. Engaging these groups in health promotion is of particular importance when seeking to target those who may benefit the most and to reduce health inequalities. This study aimed to explore what influences them practicing health promotion and elicit the views of cross-sector professionals with experiences of working with 'hard to reach' older people, to help inform best practice on engagement. Methods 'Hard to reach' older people were recruited through primary care by approaching those not attending for preventative healthcare, and via day centres. Nineteen participated in an interview (n = 15) or focus group (n = 4); including some overlaps: 17 were from a deprived area, 12 from BME groups, and five were oldest old. Cross-sector health promotion professionals across England with experience of health promotion with older people were identified through online searches and snowball sampling. A total of 31 of these 44 professionals completed an online survey including open questions on barriers and facilitators to uptake in these groups. Thematic analysis was used to develop a framework of higher and lower level themes. Interpretations were discussed and agreed within the team. Results Older people's motivation to stay healthy and independent reflected their everyday behaviour including practicing activities to feel or stay well, level of social engagement, and enthusiasm for and belief in health promotion. All of the oldest old reported trying to live healthily, often facilitated by others, yet sometimes being restricted due to poor health. Most older people from BME groups reported a strong wish to remain independent which was often positively influenced by their social network. Older people living in deprived areas reported reluctance to undertake health promotion activities, conveyed apathy and reported little social interaction. Cross-sector health professionals consistently reported similar themes as the older people, reinforcing the views of the older people through examples. Conclusions The study shows some shared themes across the three 'hard-to-reach' groups but also some distinct differences, suggesting that a carefully outlined strategy should be considered to reach successfully the group targeted.